The Farthest Shore - Le Guin, Ursula K. 1929- (New York : Atheneum Books for Young Readers, 2012)
A young prince joins forces with a master wizard on a journey to discover a cause and remedy for the loss of magic in Earthsea. Darkness Threatens to overtake Earthsea. As the world and its wizards are losing their magic, Ged -- powerful Archmage, wizard, and dragonlord -- embarks on a sailing journey with highborn young prince, Arren. They travel far beyond the realm of death to discover the cause of these evil disturbances and to restore magic to a land desperately thirsty for it.
Rowan tree -- Masters of Roke -- Hort town -- Magelight -- Sea dreams -- Lorbanery -- Madman -- Children of the open sea -- Orm Embar -- Dragons' run -- Selidor -- Dry land -- Stone of pain.
Keywords: Magic -- Juvenile fiction; Magic -- Fiction; Fantasy fiction